Effect Percentage of Seam Carving Implementation on Image Based on Texture Characteristics Using GLCM - Wahyudi, Muhammad; Purwadi, Hari; Putra, Arief Bramanto Wicaksono (Jurusan Teknik Elektro Universitas Negeri Semarang, 2020)
flexibility of the appearance of electronic devices currently causes new demands on digital media, especially for the provision of content. Until now, images, although an important element in digital media, usually remain rigid in terms of size and cannot change size so that they cannot adjust to different layouts automatically. The solution to overcome this problem is by resizing the image. One method that works well for resizing images is seam carving. Seam carving aims to resize the image by not eliminating important content in the image. This study aims to see the effect of changing the texture of seam carving images to images that have different levels of complexity. The trial was conducted by comparing the original image and seam carving image. Seam carving image used is differentiated based on the ratio scale, which is 10%, 20%, 30%, 40%, 50%. Testing is done by processing 4 image samples using the Gray Level Co-Occurence Matrix (GLCM) method including Contrast, Correlation, Energy and Homogeneity. Then testing is done by comparing the original image with seam carving image using the features of GLCM. From the test results it can be concluded that seam carving as a method of resizing images can work well, with the comparison of textures using GLCM the highest level of similarity reaches 98% and the lowest is 86%.